Composite phase change heat storage asphalt pavement material and preparation method thereof
By using a composite phase change heat storage material composed of modified silica aerogel and polyethylene glycol in asphalt pavement, the durability problem of traditional asphalt pavement during temperature changes is solved, and the durability of asphalt pavement is improved and The performance of the use enhances the heat storage effect.
Patent Information
- Application Number
- CN202411427930.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-03
AI Technical Summary
Traditional asphalt pavement is prone to soften or crack when temperature changes, resulting in a decrease in service life, and the compatibility of phase-change heat storage materials with asphalt is poor, affecting the heat storage effect.
Using composite phase change heat storage asphalt pavement materials, including 55-80 parts of asphalt gravel and 8-12 parts of composite phase change heat storage materials, the composite phase change heat storage materials are made of modified silica aerogel and polyethylene glycol Composition, modified silica aerogel is prepared by nanoscale materials and sol-gel method, with good adsorption properties and specific surface area, enhancing the binding with asphalt.
It improves the durability and service performance of the road surface, enhances the energy of heat storage and heat release, reduces the impact of temperature changes on the road surface, and extends the service life of the asphalt pavement.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of road engineering materials, and more specifically, to a composite phase-change heat storage asphalt pavement material and a preparation method thereof. Background Art
[0002] With the acceleration of urbanization, asphalt pavement is the most widely used high-grade pavement in road construction because of its flatness and durability. Asphalt binder improves the ability of paving aggregate to resist damage from driving and natural factors to the pavement, making the pavement flat, dust-free, impermeable and durable.
[0003] Traditional asphalt pavements are easily softened by high temperatures in summer and easily cracked by low temperatures in winter. When used for a long time, asphalt pavements are repeatedly heated and cooled due to changes in the external ambient temperature, which affects the service life and performance of the asphalt pavement and reduces its durability. At the same time, after long-term use, the mechanical properties of the asphalt pavement are reduced.
[0004] Phase change heat storage materials can absorb or release heat within a specific temperature range. Adding phase change heat storage materials to asphalt pavement can effectively adjust the pavement temperature, thereby reducing the impact of the external ambient temperature on the asphalt pavement and improving the durability and performance of the pavement. However, the compatibility of phase change heat storage materials with asphalt is poor and they are easily separated from asphalt materials, affecting the heat storage effect of the phase change heat storage materials and the performance of the asphalt pavement. Summary of the invention
[0005] In order to improve the durability and mechanical properties of asphalt pavement, the present application provides a composite phase change heat storage asphalt pavement material and a preparation method thereof.
[0006] In the first aspect, the present application provides a composite phase change heat storage asphalt pavement material, which adopts the following technical scheme: a composite phase change heat storage asphalt pavement material, comprising the following raw materials in parts by weight: 55-80 parts of asphalt gravel, 8-12 parts of composite phase change heat storage material; the composite phase change heat storage material comprises polyethylene glycol and modified silica aerogel.
[0007] By adopting the above technical scheme, the modified silica aerogel is a nano-scale material with good adsorption performance, so that in the process of polyethylene glycol absorbing heat and undergoing phase change, the modified silica aerogel can coat and seal the polyethylene glycol, making it less likely for the polyethylene glycol to leak. At the same time, the modified silica aerogel has a small particle size and can be evenly dispersed in asphalt, and better combined with the asphalt pavement, thereby improving the durability and performance of the pavement. After the silica aerogel is modified, the specific surface area of the aerogel is increased, so that the content of polyethylene glycol loaded by the modified silica aerogel is increased, thereby increasing the phase change latent heat of the composite phase change heat storage material, which can better regulate the road surface temperature and increase the energy of heat storage and heat release.
[0008] Preferably, the mass ratio of the polyethylene glycol to the modified silica aerogel is (1.2-1.8):(0.5-1.3).
[0009] By adopting the above technical solution and controlling the mass ratio of polyethylene glycol and modified silica aerogel, the loading amount of polyethylene glycol can be effectively controlled, so that during the phase change process of polyethylene glycol absorbing and releasing heat, the modified silica aerogel restricts the movement of polyethylene glycol, so that it maintains a stable shape and is not prone to leakage.
[0010] Preferably, the preparation method of the modified silica aerogel comprises the following steps: ultrasonically dispersing the composite modified material in anhydrous ethanol to obtain a mixed solution, stirring and mixing the tetraethyl orthosilicate, the mixed solution and water until uniform, adding oxalic acid to adjust the pH to 3.3-3.7, stirring uniformly at 30-35°C, adding ammonia water to adjust the pH to neutral to form silica aerogel, adding anhydrous ethanol to age for 23-24 hours, adding n-hexane, replacing for 48 hours, replacing n-hexane every 11-12 hours, adding a composite solution of trimethylchlorosilane and n-hexane, reacting for 70-72 hours, drying at 50-60°C for 2-2.2 hours, drying at 80-90°C for 2-2.2 hours, drying at 110-120°C for 1-1.2 hours, and drying at 150-155°C for 1-1.1 hours to obtain the modified silica aerogel.
[0011] By adopting the above technical scheme, the silica aerogel is synthesized by the sol-gel method. The prepared silica aerogel has a porous network structure, a large specific surface area, and good adsorption performance. It can coat and block polyethylene glycol, reduce the leakage of polyethylene glycol, and enable the polyethylene glycol to undergo phase change while still maintaining a good shape.
[0012] Preferably, the composite modified material is graphene oxide with carbon nanotubes coated on the surface.
[0013] By adopting the above technical solution, graphene oxide has a flaky structure and is easy to form an interlayer, which can effectively improve the stability of the silica aerogel, thereby ensuring the service life of the silica aerogel and reducing the leakage of polyethylene glycol. The carbon nanotubes have excellent mechanical properties and can support the composite phase change heat storage material, which is beneficial to further improve the stability of the silica aerogel.
[0014] Preferably, the method for preparing graphene oxide with carbon nanotubes coated on the surface comprises the following steps: graphene oxide is pretreated to obtain an intermediate powder, acetylene is used as a precursor and a xylene solution of ferrocene is used as a catalyst, chemical vapor deposition is performed on the surface of the intermediate powder to obtain graphene oxide with carbon nanotubes coated on the surface.
[0015] By adopting the above technical solution, after acetylene is decomposed at high temperature, the carbon atoms produced by the decomposition diffuse inside the catalyst until they are saturated and precipitated to form the tube wall of the carbon nanotube, so that carbon nanotubes can grow on the surface of the graphene oxide, and finally the graphene oxide with the surface coated with carbon nanotubes is obtained, which is beneficial to improve the dispersibility of the graphene oxide, and at the same time further improves the reinforcing effect of the composite modified material on the silica aerogel.
[0016] Preferably, the pretreatment comprises the following steps: ultrasonically dispersing graphene oxide in an ethanol solution, dropping ammonia water to adjust the pH to 9-10, adding tetraethoxysilane, reacting for 15-16 hours, centrifuging and washing to obtain a centrifuge to obtain an intermediate powder.
[0017] By adopting the above technical solution, before the graphene oxide is vapor-deposited, tetraethoxysilane is hydrolyzed under alkaline conditions, and the active functional groups on the surface of the graphene oxide react with the silicon-oxygen bonds produced by the hydrolysis, so that a silicon dioxide layer is deposited on the surface of the graphene oxide. The coating of the silicon dioxide layer on the surface of the graphene oxide can effectively promote the growth of carbon nanotubes on the surface of the graphene oxide, so that the carbon nanotubes grown on the surface of the graphene oxide are uniform and regular.
[0018] Preferably, the modified silica aerogel is further subjected to the following treatment before drying: the wet silica gel obtained before drying is immersed in a hexamethyldisilazane solution for 24-25 hours.
[0019] By adopting the above technical scheme, the modified silica aerogel obtained after the silica wet gel is modified by hexamethyldisilazane and dried has a more complex nano-network structure, thereby increasing the specific surface area of the silica aerogel, thereby increasing the adsorption capacity of the modified silica aerogel on polyethylene glycol and increasing the phase change latent heat of the composite phase change heat storage material.
[0020] Preferably, the mass ratio of hexamethyldisilazane to tetraethyl orthosilicate is (0.14-0.16):1.
[0021] By adopting the above technical solution and controlling the addition amount of hexamethyldisilazane, the porosity and pore size of the modified silica aerogel can be effectively controlled, so that the porosity is uniform, the pore size is larger, the increase in specific surface area is the largest, and the adsorption amount of polyethylene glycol can be effectively increased.
[0022] In a second aspect, the present application provides a method for preparing a composite phase-change heat storage asphalt pavement material, using the following technical solution: A method for preparing a composite phase-change heat storage asphalt pavement material comprises the following steps: Preparation method of composite phase change heat storage material: After polyethylene glycol and modified silica aerogel are mixed, they are continuously stirred until the polyethylene glycol is evenly dispersed, the temperature is raised to 50-60° C., heated in a water bath and stirred, and dried after gelation to obtain a composite phase change heat storage material; The preparation method of asphalt pavement material is as follows: after mixing asphalt crushed stone with the composite phase change heat storage material, the temperature is raised to 170-185° C. and stirred evenly to obtain the asphalt pavement material.
[0023] By adopting the above technical scheme, polyethylene glycol is mixed with modified silica aerogel, so that the modified silica aerogel fully absorbs and adsorbs the polyethylene glycol, and a composite phase change heat storage material is obtained after gelation.
[0024] In summary, this application has the following beneficial effects: 1. Since the modified silica aerogel and polyethylene glycol in the present application are used as composite phase change heat storage materials, the modified silica aerogel is a nano-scale material with good adsorption properties, so that in the process of polyethylene glycol absorbing heat and undergoing phase change, the modified silica aerogel can coat and seal the polyethylene glycol, making it less likely for the polyethylene glycol to leak. At the same time, the modified silica aerogel has a small particle size and can be evenly dispersed in asphalt, and better combined with the asphalt pavement, thereby improving the durability and performance of the pavement. After the silica aerogel is modified, the specific surface area of the aerogel is increased, so that the content of polyethylene glycol loaded by the modified silica aerogel is increased, thereby increasing the phase change latent heat of the composite phase change heat storage material, being able to better regulate the pavement temperature, and increasing the energy of heat storage and heat release.
[0025] 2. In the present application, by controlling the mass ratio of polyethylene glycol and modified silica aerogel, the loading amount of polyethylene glycol can be effectively controlled, so that during the phase change of polyethylene glycol absorbing and releasing heat, the modified silica aerogel restricts the movement of polyethylene glycol, so that it maintains a stable shape and is not prone to leakage.
[0026] 3. In the present application, hexamethyldisilazane is used to modify the wet silica gel. The modified silica aerogel obtained after drying has a more complex nano-network structure, thereby increasing the specific surface area of the silica aerogel, thereby increasing the adsorption capacity of the modified silica aerogel on polyethylene glycol and increasing the phase change latent heat of the composite phase change heat storage material. DETAILED DESCRIPTION
[0027] The present application is further described in detail below with reference to the embodiments.
[0028] Preparation Examples 1-3 of Composite Modified Materials Preparation Example 1 1.12 g of graphene oxide was ultrasonically dispersed in 1 L of 90% ethanol solution, 10 wt% ammonia water was slowly added to adjust the pH to 9, and 2.23 mL of tetraethoxysilane was added. After reacting for 15 h, the centrifuged product was obtained after centrifugation and washing to obtain an intermediate powder. The intermediate powder was placed in a tube furnace, and after the temperature was raised to 650°C by introducing argon gas, a 0.05 mg / mL ferrocene solution in xylene and acetylene were introduced in sequence, with an acetylene flow rate of 50 mL / min. Chemical vapor deposition was carried out on the surface of the intermediate powder using acetylene as a precursor and the ferrocene solution in xylene as a catalyst. The deposition time was 10 min to obtain graphene oxide with carbon nanotubes coated on the surface.
[0029] Preparation Example 2 1.21 g of graphene oxide was ultrasonically dispersed in 1100 mL of 85% ethanol solution, 12 wt% ammonia water was slowly added to adjust the pH to 10, and 2.45 mL of tetraethoxysilane was added. After reacting for 16 h, the centrifugal material was obtained after centrifugation and washing to obtain an intermediate powder. The intermediate powder was placed in a tube furnace, and after the argon gas was introduced and the temperature was raised to 680°C, a 0.06 mg / mL ferrocene xylene solution and acetylene were introduced in sequence, with an acetylene flow rate of 60 mL / min. Chemical vapor deposition was carried out on the surface of the intermediate powder using acetylene as a precursor and the ferrocene xylene solution as a catalyst. The deposition time was 8 min to obtain graphene oxide with carbon nanotubes coated on the surface.
[0030] Preparation Example 3 The difference between Preparation Example 3 and Preparation Example 1 is that in Preparation Example 3, the graphene oxide is not pretreated, and an equal amount of graphene oxide is placed in a tubular furnace, and the graphene oxide is chemically vapor deposited to obtain graphene oxide with carbon nanotubes coated on the surface.
[0031] Preparation Example 4-11 of Modified Silica Aerogel Preparation Example 4 0.12 g of the composite modified material was ultrasonically dispersed in 8.69 mL of anhydrous ethanol to obtain a mixed solution. 1.23 mL of tetraethyl orthosilicate, 8.69 mL of the mixed solution and 3.81 mL of water were stirred and mixed until uniform, and then oxalic acid was added to adjust the pH to 3.3. After stirring uniformly at 30°C, 10 wt% ammonia water was added to adjust the pH to neutral to form a silica aerogel. After aging with anhydrous ethanol for 23 hours, sufficient n-hexane was added and replaced for 48 hours. The n-hexane was replaced every 12 hours. After adding a composite solution of trimethylchlorosilane and n-hexane in a mass ratio of 1:9.7, the reaction was carried out for 72 hours, and then the mixture was dried at 60°C for 2 hours, at 90°C for 2 hours, at 120°C for 1 hour, and at 155°C for 1 hour to obtain a modified silica aerogel.
[0032] In this preparation example, the composite modified material is the composite modified material prepared in Preparation Example 1.
[0033] Preparation Example 5 0.15 g of the composite modified material was ultrasonically dispersed in 10.32 mL of anhydrous ethanol to obtain a mixed solution. 1.48 mL of tetraethyl orthosilicate, 10.32 mL of the mixed solution and 4.02 mL of water were stirred and mixed until uniform, and then oxalic acid was added to adjust the pH to 3.7. After stirring uniformly at 35° C., 10 wt % ammonia water was added to adjust the pH to neutral to form a silica aerogel. After aging with anhydrous ethanol for 24 h, sufficient n-hexane was added, and after replacement for 48 h, the n-hexane was replaced every 11 h. After adding a composite solution of trimethylchlorosilane and n-hexane in a mass ratio of 1:10, the reaction was continued for 70 h, and then the mixture was dried at 50° C. for 2.2 h, at 80° C. for 2.2 h, at 110° C. for 1.2 h, and at 150° C. for 1.1 h to obtain a modified silica aerogel.
[0034] In this preparation example, the composite modified material is the composite modified material prepared in Preparation Example 2.
[0035] Preparation Example 6 The difference between Preparation Example 6 and Preparation Example 4 is that in Preparation Example 6, the composite modified material is the composite modified material prepared in Preparation Example 3.
[0036] Preparation Example 7 The difference between Preparation Example 7 and Preparation Example 4 is that in Preparation Example 7, the composite modified material is graphene oxide that is not coated with carbon nanotubes.
[0037] Preparation Example 8 The difference between Preparation Example 8 and Preparation Example 4 is that in Preparation Example 8, the modified silica aerogel is further treated as follows before drying: the wet silica gel obtained before drying is immersed in a hexamethyldisilazane solution for 24 hours, and the mass ratio of hexamethyldisilazane to ethyl orthosilicate is 0.16:1.
[0038] Preparation Example 9 The difference between Preparation Example 9 and Preparation Example 4 is that in Preparation Example 9, the modified silica aerogel is further treated as follows before drying: the wet silica gel obtained before drying is immersed in a hexamethyldisilazane solution for 24-25 hours, and the mass ratio of hexamethyldisilazane to ethyl orthosilicate is 0.14:1.
[0039] Preparation Example 10 The difference between Preparation Example 10 and Preparation Example 8 is that in Preparation Example 10, the mass ratio of hexamethyldisilane to ethyl orthosilicate is 0.1:1.
[0040] Preparation Example 11 The difference between Preparation Example 11 and Preparation Example 8 is that in Preparation Example 11, the mass ratio of hexamethyldisilane to ethyl orthosilicate is 0.25:1. Example
[0041] Example 1 A composite phase-change heat storage asphalt pavement material comprises the following raw materials in parts by weight: 55 kg of asphalt gravel and 8 kg of composite phase-change heat storage material, wherein the composite phase-change heat storage material comprises polyethylene glycol and modified silica aerogel in a mass ratio of 1.2:1.3, and the modified silica aerogel is the modified silica aerogel prepared in Preparation Example 4.
[0042] The method for preparing the composite phase change heat storage asphalt pavement material comprises the following steps: Preparation method of composite phase change heat storage material: After polyethylene glycol and modified silica aerogel are mixed, they are continuously stirred until the polyethylene glycol is evenly dispersed, the temperature is raised to 50° C., heated in a water bath and stirred, and dried after gelation to obtain a composite phase change heat storage material; Preparation method of asphalt pavement material: After mixing asphalt crushed stone with the composite phase change heat storage material, heating it to 170° C. and stirring it evenly, the asphalt pavement material is obtained.
[0043] Example 2 A composite phase-change heat storage asphalt pavement material comprises the following raw materials in parts by weight: 80 kg of asphalt gravel and 12 kg of a composite phase-change heat storage material, wherein the composite phase-change heat storage material comprises polyethylene glycol and modified silica aerogel in a mass ratio of 1.8:0.5, and the modified silica aerogel is the modified silica aerogel prepared in Preparation Example 5.
[0044] The method for preparing the composite phase change heat storage asphalt pavement material comprises the following steps: Preparation method of composite phase change heat storage material: After polyethylene glycol and modified silica aerogel are mixed, they are continuously stirred until the polyethylene glycol is evenly dispersed, the temperature is raised to 60° C., heated in a water bath and stirred, and dried after gelation to obtain a composite phase change heat storage material; Preparation method of asphalt pavement material: After mixing asphalt crushed stone with the composite phase change heat storage material, heating it to 185° C. and stirring it evenly, the asphalt pavement material is obtained.
[0045] Example 3 The difference between Example 3 and Example 1 is that in Example 3, the modified silica aerogel is the modified silica aerogel prepared in Preparation Example 6.
[0046] Example 4 The difference between Example 4 and Example 1 is that in Example 4, the modified silica aerogel is the modified silica aerogel prepared in Preparation Example 7.
[0047] Example 5 The difference between Example 5 and Example 1 is that in Example 5, the modified silica aerogel is the modified silica aerogel prepared in Preparation Example 8.
[0048] Example 6 The difference between Example 6 and Example 1 is that in Example 6, the modified silica aerogel is the modified silica aerogel prepared in Preparation Example 9.
[0049] Example 7 The difference between Example 7 and Example 1 is that in Example 7, the modified silica aerogel is the modified silica aerogel prepared in Preparation Example 10.
[0050] Example 8 The difference between Example 8 and Example 1 is that in Example 8, the modified silica aerogel is the modified silica aerogel prepared in Preparation Example 11.
[0051] Example 9 The difference between Example 9 and Example 1 is that in Example 9, an equal amount of silica aerogel is used to replace the modified silica aerogel. The preparation method of silica aerogel comprises the following steps: 1.23 mL of tetraethyl orthosilicate, 8.69 mL of anhydrous ethanol and 3.81 mL of water are stirred and mixed until uniform, oxalic acid is added to adjust the pH to 3.3, and after stirring uniformly at 30°C, 10 wt% ammonia water is added to adjust the pH to neutral to form silica aerogel, and anhydrous ethanol is added to age for 23 hours, and then sufficient n-hexane is added and replaced for 48 hours, and the n-hexane is replaced every 12 hours. After adding a composite solution of trimethylchlorosilane and n-hexane in a mass ratio of 1:9.7, react for 72 hours, dry at 60°C for 2 hours, dry at 90°C for 2 hours, dry at 120°C for 1 hour, and dry at 155°C for 1 hour to obtain silica aerogel.
[0052] Example 10 The difference between Example 10 and Example 1 is that in Example 10, the mass ratio of polyethylene glycol to modified silica aerogel is 0.2:1.3.
[0053] Embodiment 11 The difference between Example 11 and Example 1 is that in Example 11, the mass ratio of polyethylene glycol to modified silica aerogel is 7:1.3.
[0054] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, an equal amount of asphalt crushed stone is used instead of the composite phase change heat storage material.
[0055] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, an equal amount of polyethylene glycol is used instead of the composite phase change heat storage material.
[0056] Detection Methods According to the raw materials and preparation methods of Examples 1-11 and Comparative Examples 1-2, composite phase-change heat storage asphalt pavement materials were prepared, and the phase change latent heat of the materials was detected using the STA-449A comprehensive synchronous thermal analyzer of Beijing AVIC Times Instrument Equipment Co., Ltd., and the results are recorded in Table 1; Cooling performance test: The composite phase change heat storage asphalt pavement materials prepared by Examples 1-11 and Comparative Examples 1-2 were placed in a simulation box at an ambient temperature of 80°C for 1 hour, and the maximum temperature of each sample was recorded. The difference between the maximum temperature of each sample and the maximum temperature of Comparative Example 1 was calculated based on Comparative Example 1. A value higher than Comparative Example 1 was recorded as +, and a value lower than Comparative Example 1 was recorded as -. The results are recorded in Table 1.
[0057] Table 1 Performance test of composite phase change heat storage asphalt pavement material project Latent heat of phase change / (J / g) Temperature drop difference / ℃ Example 1 171 -5.61 Example 2 238 -6.58 Example 3 159 -4.66 Example 4 151 -4.62 Example 5 198 -5.89 Example 6 196 -6.01 Example 7 179 -5.06 Example 8 176 -4.98 Example 9 143 -4.26 Example 10 162 -4.58 Embodiment 11 159 -4.67 Comparative Example 1 65 0 Comparative Example 2 84 -0.96 According to Table 1, Examples 1-2 and Comparative Example 1, it can be seen that the pavement material prepared in Examples 1-2 has better phase change latent heat than that in Comparative Example 1, and at the same time, the temperature drop difference is lower, indicating that the pavement material prepared in Examples 1-2 has better phase change latent heat, and the phase change material can reduce the temperature of the pavement material when the pavement material absorbs heat, thereby reducing the damage to the pavement due to high temperature.
[0058] In Example 1-2, modified silica aerogel and polyethylene glycol are used to prepare a composite phase change heat storage material. The modified silica aerogel is a nano-scale material with the characteristics of large specific surface area and good adsorption performance. When the asphalt pavement is heated, the polyethylene glycol can absorb heat and undergo phase change, thereby reducing the temperature rise of the asphalt pavement. The modified silica aerogel can coat and seal the polyethylene glycol, making it less likely to leak. At the same time, the modified silica aerogel has a small particle size and can be evenly dispersed in the asphalt, and has better integration with the asphalt pavement, thereby improving the durability and performance of the asphalt pavement. After the silica aerogel is modified, the adsorption performance is further improved, and it can load more polyethylene glycol, thereby increasing the phase change latent heat of the composite phase change heat storage material, thereby better regulating the pavement temperature and improving the durability and service life of the asphalt pavement.
[0059] Compared with Example 1, Example 3 has a lower phase change latent heat and a smaller temperature drop difference, indicating that the performance of the pavement material obtained in Example 3 is reduced. In Example 3, the graphene oxide is not pretreated before chemical vapor deposition. After the graphene oxide is pretreated, the hydrolysis of tetraethylsilane can deposit a silicon dioxide layer on the surface of the graphene oxide. The silicon dioxide layer can effectively promote the growth of carbon nanotubes on the surface of the graphene oxide, so that the carbon nanotubes grown on the surface of the graphene oxide are uniform and regular. The graphene oxide with carbon nanotubes coated on the surface has a better morphology and a larger specific surface area, which can increase the polyethylene glycol loading amount of the modified silica aerogel, thereby increasing the phase change latent heat.
[0060] Compared with Example 1, Example 4 has a lower phase change latent heat and a smaller temperature drop difference, indicating that the performance of the pavement material obtained in Example 4 is reduced. In Example 4, the graphene oxide is not coated with carbon nanotubes. The graphene oxide has a flaky structure and is easy to form an interlayer, which can effectively improve the stability of the silica aerogel, increase the service life of the modified silica aerogel, and reduce the leakage of polyethylene glycol. The tubular structure and excellent mechanical properties of the carbon nanotubes can support the composite phase change heat storage material and further improve the stability of the silica aerogel. The graphene oxide in Example 4 is not coated with carbon nanotubes, and the stability of the obtained modified silica aerogel is reduced, thereby reducing the stability of the composite phase change heat storage material of the asphalt pavement and weakening the effect.
[0061] Compared with Example 1, the phase change latent heat of Example 5-6 is increased and the temperature drop difference is increased, indicating that the performance of the pavement material obtained in Example 5-6 is improved. In Example 5-6, the modified silica aerogel is modified with hexamethyldisilazane before drying. The modified silica aerogel obtained from the silica wet gel treated with hexamethyldisilazane has a more complex nano-network structure, which can further increase the specific surface area of the modified silica aerogel, thereby increasing the adsorption amount of polyethylene glycol by the modified silica aerogel, thereby improving the heat storage performance of the composite phase change heat storage material, thereby improving the performance and durability of the asphalt pavement.
[0062] Compared with Example 5, the phase change latent heat of Example 7-8 is reduced and the temperature drop difference is reduced, indicating that the performance of the pavement material prepared in Example 7-8 is reduced compared with that in Example 5. Example 7-8 adjusts the amount of hexamethyldisilazane used. The amount of hexamethyldisilazane used directly affects the porosity and pore size of the modified silica aerogel. Too high or too low an amount of hexamethyldisilazane used can easily make the porosity of the modified silica aerogel uneven and the specific surface area decrease compared with that in Example 5, thereby reducing the adsorption amount of polyethylene glycol.
[0063] Compared with Example 1, Example 9 has a lower phase change latent heat and a smaller temperature drop difference, indicating that the performance of the pavement material prepared in Example 9 is lower than that in Example 1. Unmodified ordinary silica aerogel is used in Example 9, and the ordinary silica aerogel is modified so that the aerogel has a smaller specific surface area than the modified silica aerogel used in Example 1, and the amount of polyethylene glycol loaded in the silica aerogel is reduced, thereby reducing the phase change heat storage of the asphalt pavement.
[0064] Compared with Example 1, the phase change latent heat of Example 10-11 is reduced and the temperature drop difference is reduced, indicating that the performance of the pavement material prepared in Example 10-11 is reduced. In Example 10-11, the mass ratio of polyethylene glycol to modified silica aerogel is changed. The modified silica aerogel can load polyethylene glycol, so that when the polyethylene glycol undergoes a phase change, the modified silica aerogel can restrict the polyethylene glycol to maintain a stable shape and is not prone to leakage. Changing the mass ratio of polyethylene glycol to modified silica aerogel can easily result in too little or too much loading of the modified silica aerogel, which is not conducive to the effect of the composite phase change heat storage material.
[0065] Compared with Example 1, the phase change latent heat of Comparative Example 2 is reduced and the temperature drop difference is reduced, indicating that the performance of the pavement material prepared in Comparative Example 2 is reduced. In Comparative Example 2, modified silica aerogel is not added as a carrier of polyethylene glycol. The polyethylene glycol loses the coating of the modified silica aerogel, which makes it easy to leak when the polyethylene glycol undergoes a phase change, thereby affecting the performance and normal use of the asphalt pavement.
[0066] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A composite phase change heat storage asphalt pavement material, characterized by: The invention comprises the following raw materials in parts by weight: 55-80 parts of asphalt crushed stone and 8-12 parts of composite phase-change heat storage material; the composite phase-change heat storage material comprises polyethylene glycol and modified silica aerogel.
2. The composite phase change heat storage asphalt pavement material according to claim 1, characterized in that: The mass ratio of the polyethylene glycol to the modified silica aerogel is (1.2-1.8):(0.5-1.3).
3. The composite phase change heat storage asphalt pavement material according to claim 1, characterized in that: The preparation method of the modified silica aerogel comprises the following steps: ultrasonically dispersing a composite modified material in anhydrous ethanol to obtain a mixed solution, stirring and mixing tetraethyl orthosilicate, the mixed solution and water until uniform, adding oxalic acid to adjust the pH to 3.3-3.7, stirring uniformly at 30-35°C, adding ammonia water to adjust the pH to neutral to form silica aerogel, adding anhydrous ethanol to age for 23-24 hours, adding n-hexane to replace for 48 hours, replacing the n-hexane every 11-12 hours, adding a composite solution of trimethylchlorosilane and n-hexane, reacting for 70-72 hours, drying at 50-60°C for 2-2.2 hours, drying at 80-90°C for 2-2.2 hours, drying at 110-120°C for 1-1.2 hours, and drying at 150-155°C for 1-1.1 hours to obtain the modified silica aerogel.
4. The composite phase change heat storage asphalt pavement material according to claim 3, characterized in that: The composite modified material is graphene oxide with carbon nanotubes coated on the surface.
5. A composite phase-change heat storage asphalt pavement material and a preparation method thereof according to claim 4, characterized in that: The method for preparing graphene oxide with carbon nanotubes coated on the surface comprises the following steps: preparing intermediate powder by pre-treating graphene oxide, performing chemical vapor deposition on the surface of the intermediate powder with acetylene as a precursor and a xylene solution of ferrocene as a catalyst, and obtaining graphene oxide with carbon nanotubes coated on the surface.
6. The composite phase change heat storage asphalt pavement material according to claim 5, characterized in that: The pretreatment comprises the following steps: ultrasonically dispersing graphene oxide in an ethanol solution, dropping ammonia water to adjust the pH to 9-10, adding tetraethoxysilane, reacting for 15-16 hours, centrifuging and washing to obtain a centrifuge to obtain an intermediate powder.
7. The composite phase change heat storage asphalt pavement material according to claim 3, characterized in that: Before drying, the modified silica aerogel is further treated as follows: the wet silica gel obtained before drying is immersed in a hexamethyldisilazane solution for 24-25 hours.
8. The composite phase change heat storage asphalt pavement material according to claim 7, characterized in that: The mass ratio of hexamethyldisilane to ethyl orthosilicate is (0.14-0.16):
1.
9. A method for preparing a composite phase-change heat storage asphalt pavement material according to any one of claims 1 to 8, characterized in that: The following steps are involved: Preparation method of composite phase change heat storage material: After polyethylene glycol and modified silica aerogel are mixed, they are continuously stirred until the polyethylene glycol is evenly dispersed, the temperature is raised to 50-60° C., heated in a water bath and stirred, and dried after gelation to obtain a composite phase change heat storage material; The preparation method of asphalt pavement material is as follows: after mixing asphalt crushed stone with the composite phase change heat storage material, the temperature is raised to 170-185° C. and stirred evenly to obtain the asphalt pavement material.
Citation Information
Cited By
Polyvinyl chloride environment-friendly efficient flame retardant and preparation method thereof
CN120230354A
